The Cauchy Problem for a Class of Coupled Systems Containing a Convolution Operator (Journal of Partial Differential Equations, 2003)
" Some results on the invariant regions ,existence and uniqueness of solutions to a class of integrodifferential systems are established. Applying these results to integrodifferential systems with a small parameter \u03b5 > 0, we obtain,in particular, some estimates of solutions uniform in \u03b5 > 0."